Implementasi Enterprise Resource Planning (Erp) Odoo 16 Modul Sales pada Proses Bisnis Penyewan Gudang di PT.X - Rochmatul Amalia; Hafid Syaifullah (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
X is a Warehouse Distributor (WMS/Warehouse Management System) company that provides sales of warehouse services, this activity is very important to make the warehouse run smoothly and according to expectations. With the capabilities it has, for monthly reports the company has not been able to fulfill user requests. Therefore PT. X tries to fulfill user requests by using the ERP implementation concept. On business processes at PT. X is carried out using Odoo software. By using this Odoo implementation, all data from several different business modules can be integrated. The use of this method is required for the implementation of the Sales module. The purpose of this research is to find out sales reports that are carried out manually in the warehouse rental sales process so that they provide effective, efficient and optimal results in the warehouse rental process. The results of this research can be concluded that the Sales module for creating Outstanding Sales Orders with Odoo Software will make it easier for business process activities to be carried out effectively and efficiently.